2011
DOI: 10.1113/jphysiol.2011.217307
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of functional serotonin 5‐HT3 receptors by glutamatergic granule cells in the early postnatal mouse cerebellum

Abstract: Non-technical summary The serotonin 3 receptor is a ligand-gated ion channel which is activated by the neurotransmitter serotonin. This receptor is present in many parts of the brain, yet there is hardly any information on its function in the cerebellum. In this study, we use transgenic mice to show that the serotonin 3 receptor is localised in the cerebellum during the first three weeks after birth. We found that during this period, the serotonin 3 receptor regulates communication between two major types of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…To visualize neurons in ZI that contained GABA, coronal sections were processed for glutamic acid decarboxylase (GAD) using procedures adapted from previous reports (Oostland et al, 2011;Aligny et al, 2014). The sections were rinsed in 0.1 M PBS for 20 min before being placed in a PBS-based blocking solution that contained 0.3 M glycine, 5% goat serum, 1% bovine serum albumin, and 0.1% Triton X-100, pH 7.4, at room temperature for 1 h. Sections were then incubated overnight with polyclonal rabbit anti-GAD 65/67 antibody (1:250, ab49832, Abcam) diluted in PBS at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…To visualize neurons in ZI that contained GABA, coronal sections were processed for glutamic acid decarboxylase (GAD) using procedures adapted from previous reports (Oostland et al, 2011;Aligny et al, 2014). The sections were rinsed in 0.1 M PBS for 20 min before being placed in a PBS-based blocking solution that contained 0.3 M glycine, 5% goat serum, 1% bovine serum albumin, and 0.1% Triton X-100, pH 7.4, at room temperature for 1 h. Sections were then incubated overnight with polyclonal rabbit anti-GAD 65/67 antibody (1:250, ab49832, Abcam) diluted in PBS at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…During early development, the cerebellum exhibits a transient expression of 5-HT1 and 5-HT3 receptors, which play an important role in the formation of the cerebellar neuronal network (Miquel et al, 1994; Oostland et al, 2011). This may offer the possible mechanism behind a compromised serotonergic system during development and subsequent cerebellar abnormalities in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, serotonergic fibers have a greater density in vermal lobules VII to X in rats (Bishop and Ho, 1985), while the greatest density in opossum was noted in VIII to IX and lowest in lobules II to V (Bishop et al, 1985). Even during development, the postnatal transient expression of 5-HT3 receptors is relatively high in lobules I to VI and lesser in lobules VII to X (Oostland et al, 2011). These lines of information suggest that individual cerebellar lobules may have a varying sensitivity to 5-HT homeostasis, and could be the mechanism behind the lobule-specific effects we observed in MAO-A Neo mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in 5-HT 3A /EGFP transgenic mice have revealed that the expression pattern of 5-HT 3 R at P7 follows the migration pathway of the cerebellar granule cells from the external to the internal granule cell layer; then, by P14, the expression starts to decrease and becomes completely absent after P21 [138]. In contrast, no coexpression of 5-HT 3 receptors has been found with glial cells, PCs, and interneurons.…”
Section: The Role Of the Serotonergic System In The Development Mmentioning
confidence: 99%